2017
DOI: 10.7150/thno.17366
|View full text |Cite
|
Sign up to set email alerts
|

Theranostic Nucleic Acid Binding Nanoprobe Exerts Anti-inflammatory and Cytoprotective Effects in Ischemic Injury

Abstract: Extracellular nucleic acids are proinflammatory molecules that have been implicated in a diverse range of diseases. We report here the development of a multivalent nucleic acid scavenging nanoprobe, where the fluorochrome thiazole orange (TO) is conjugated to a polymeric 40 kDa dextran carrier. Dextran-TO (Dex-TO) has nanomolar affinity for mammalian and bacterial nucleic acids and attenuates the production of inflammatory cytokines from activated macrophages exposed to DNA and RNA. Mice with myocardial ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 36 publications
(36 reference statements)
0
18
0
Order By: Relevance
“…Recently, new therapies emerged for regulating inflammation. For example, the canakinumab, which inhibits the IL-1β innate immunity pathway, significantly reduced the rate of recurrent cardiovascular events, but had a lower heart-targeting effect 36 ; theranostic nucleic acid-binding nanoprobes were shown to exert anti-inflammatory and cytoprotective effects in ischemic injury 37 ; platelet-targeted delivery of peripheral blood mononuclear cells to the ischemic heart restored cardiac function after I/R injury 38 . Clearly, this field is in its infancy, and a concerted effort is needed to develop effective therapies to modify inflammation rationally.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, new therapies emerged for regulating inflammation. For example, the canakinumab, which inhibits the IL-1β innate immunity pathway, significantly reduced the rate of recurrent cardiovascular events, but had a lower heart-targeting effect 36 ; theranostic nucleic acid-binding nanoprobes were shown to exert anti-inflammatory and cytoprotective effects in ischemic injury 37 ; platelet-targeted delivery of peripheral blood mononuclear cells to the ischemic heart restored cardiac function after I/R injury 38 . Clearly, this field is in its infancy, and a concerted effort is needed to develop effective therapies to modify inflammation rationally.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated that cellular nucleic acids such as RNA and miRNA are released from the heart following myocardial ischemic injury ( 4 , 5 , 7 , 34 36 ). The cellular RNA, once released from the cells, can be highly proinflammatory by inducing cytokine production and innate immune cell activation ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a key component of myocardial ischemic injury ( 1 ). Studies have shown that nucleic acids such as cellular RNAs, including microRNAs (miRNAs), are released from initial tissue injury within the myocardium ( 2 4 ) and may contribute to the increased myocardial inflammation following ischemia-reperfusion (I/R) injury ( 4 , 5 ). Systemic administration of nucleic acid binding nanoprobe ( 5 ) or RNase ( 4 , 6 ) leads to reduced myocardial inflammation and infarction, likely by reducing extracellular (ex) RNA levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others developed a multivalent nucleic acid scavenging nanoprobe, fluorochrome thiazole orange conjugated to a dextran carrier (Dex-TO), to scavenge nucleic acids. Dex-TO was administered intravenously to mice subjected to MI, initially at the onset of IRI and again 4 h later, resulting in a reduced inflammation and a decrease in IS in the Dex-TO treated mice ( 57 ).…”
Section: Damage-associated Molecular Patterns Related To Myocardial Imentioning
confidence: 99%